Research of Flexible and Wearable Solar Cells - Chu, Yiwei (Transactions on Computer Science and Intelligent Systems Research, 2024)
Solar power has been widely acknowledged to be the purest and most economical power in the 21 st century. Flexible wearable solar cells are becoming the first choice for power generation because of their high power to weight ratio, stable mechanics, affordable and practical applications. Additionally, the rapid advancement of wearable devices and transport has created a need for flexible and portable power sources with adequate mechanical stability to support such advanced technologies. Flexible, wearable PV devices provide the perfect way to solve the problem. This paper gives a summary of recent studies and advances in the area of flexible wearable solar cells. I classify the PV modules into 5 categories – fiber, organic, GaAs, perovskite-based, and metal-dichalcogenide, and discuss their mechanism, operating principle, optics, and latest developments. In the end, I give an overview of the techniques and suggest their possible use in the future.